Creating an environment for collaborative language learning - Dunworth, Katie (HERDSA, 2002)
This paper describes the development and implementation of a project to encourage collaborative teaching practices and reciprocal peer learning in the area of tertiary-level language education. Preliminary analysis of student need in the form of survey research revealed a strong level of support for the project, which was subsequently conducted over a period of three years. The project illustrates the nexus between the professional development of academic staff and the value of the learning experience of students.